To simplify the given expression, we start by rewriting it for clarity. The expression is:
\[ \frac{3 + (-3)}{-3 + 1} + \frac{9^{1 - 3^2}}{-7 - 8} \]
Let's simplify each part step by step:
Step 1: Simplify the first fraction
-
Numerator: \[ 3 + (-3) = 0 \]
-
Denominator: \[ -3 + 1 = -2 \]
Putting it together, the first fraction becomes: \[ \frac{0}{-2} = 0 \]
Step 2: Simplify the second fraction
-
Exponent Simplification: \[ 3^2 = 9 \] Therefore: \[ 1 - 3^2 = 1 - 9 = -8 \]
-
Calculating \(9^{-8}\): \[ 9^{-8} = \frac{1}{9^8} \]
-
Denominator: \[ -7 - 8 = -15 \]
Now, substituting: \[ \frac{9^{-8}}{-15} = \frac{1/9^8}{-15} = -\frac{1}{15 \cdot 9^8} \]
Step 3: Combine both parts
Now we put together the simplified parts: \[ 0 + \left(-\frac{1}{15 \cdot 9^8}\right) = -\frac{1}{15 \cdot 9^8} \]
Conclusion
Thus, the simplified expression is: \[ -\frac{1}{15 \cdot 9^8} \]